Emerging role of the KRAS-PDK1 axis in pancreatic cancer - Ferro, R.; Falasca, Marco (Baishideng BioMed Scientific Co., Ltd, 2014)
Pancreatic cancer is a highly aggressive tumour that is very resistant to treatments and it is rarely diagnosed early because of absence of specific symptoms. Therefore, the prognosis for this disease is very poor and it has the grim supremacy in terms of unfavourable survival rates. There have been great advances in survival rates for many types of cancers over the past few decades but hardly any change for pancreatic cancer. Mutations of the Ras oncogene are the most frequent oncogenic alterations in human cancers. The frequency of KRAS mutations in pancreatic cancer is around 90%. Given the well-established role of KRAS in cancer it is not surprising that it is one of the most attractive targets for cancer therapy. Nevertheless, during the last thirty years all attempts to target directly KRAS protein have failed. Therefore, it is crucial to identify downstream KRAS effectors in order to develop specific drugs able to counteract activation of this pathway. Among the different signalling pathways activated by oncogenic KRAS, the phosphoinositide 3-Kinase (PI3K) pathway is emerging as one of the most critical KRAS effector. In turn, PI3K activates several parallel pathways making the identification of the precise effectors activated by KRAS/PI3K more difficult. Recent data identify 3-phosphoinositide-dependent protein kinase 1 as a key tumour-initiating event downstream KRAS interaction with PI3K in pancreatic cancer.